Effects of Responsive Electrical Brain Stimulation on Intracranial Electroencephalogram Spikes. Issue 4 (5th August 2013) - Labar, Douglas; Dakov, Pepi; Kobylarz, Erik; Nikolov, Blagovest; Schwartz, Theodore H.; Fisher, Stanley
<x xml:space="preserve">Abstract</x> Objectives Responsive cortical electrical stimulation with implanted devices is under investigation for seizures. While designed to terminate seizures, might this stimulation also affect the underlying epileptic process of seizure generation? Materials and Methods Four patients undergoing intracranial electroencephalogram (EEG) for seizure localization had an external responsive neurostimulator (eRNS) connected to their seizure‐onset zones. The eRNS detected interictal EEG spikes and stimulated at the focus. We quantified spikes at three locations: 1) near stimulation, 2) remote but in the same lobe as stimulation, and (3) in different lobe from stimulation. Ten‐minute windows were analyzed at three times: 1) baseline, 2) after the first four hours of stimulation, and 3) poststimulation. One blinded investigator performed manual spike counts. Quantitative measures were total spikes, spike‐free intervals (continuous ten‐sec segments with no spikes), and spike clusters (one‐sec intervals with three or more spikes). Results Some changes in spikes occurred in each patient, but no uniform pattern emerged. Two general observations were made: 1) spike counts within a given patient exhibited internally consistent changes with stimulation; 2) across patients, the nature of spike count changes varied, indicating patient‐to‐patient variability. For example, poststimulation, two patients had more and two patients had fewer total spikes. However, when spikes decreased near stimulation, they decreased at other sites, and when spikes increased near stimulation, they increased at other sites. Conclusions Changes in spike occurrence, organization, and topography with stimulation suggest the eRNS affected spike generation and may affect the underlying interictal epileptic process. Case‐to‐case variability may be due to individual patient factors, and its significance is yet to be determined.